(untitled) (Revista Torreón Universitario, 2022)
The objective of this article is to represent the relationship of intergenerational teams with productivity, competitiveness, leadership, and conflict management in organizations, and thus to know the impact they generate in the fulfillment of objectives. Through a bibliographic search, 50 articles were extracted, of which 12 were selected for review and analysis. The results of the analysis highlight the task of the company to manage the aspects that surround its staff, contemplate the different ways of acting and thinking of the generations, take advantage of the skills of each person to improve the development of human capital, promote the exchange of ideas and knowledge between generations to obtain creative solutions that favor the productivity of the organization.